PENERAPAN WAKAF UANG OLEH BADAN WAKAF MANDIRI - Devi Andrianingsih (STAI AN-NAJAH INDONESIA MANDIRI, 2020)
The Mandiri Waqf Board is an institution that is dedicated to improving the welfare of the community, especially the Orphans and Dhuafa by raising and managing waqf resources productively. The cash waqf that has been collected by the Mandiri Waqf Board is managed and channeled through educational programs such as the construction of the Tahfidz House building, and in the economic sector the cash waqf is earmarked for the development of chicken and catfish farms. Based on this, the authors formulated the problem in this study regarding how the cash waqf management system carried out by the Independent Waqf Board in the process of developing chicken and catfish farms. This research is a descriptive-qualitative research. Data obtained from the General Manager of Waqf, waqf admin staff, and farm managers. Secondary data are reference books that will complement the existing documentation. The data collection methods that the writer uses are interviews and observations. The results of research on the application of the cash waqf system carried out by the Mandiri Waqf Board show that the productive use of cash waqf has a dual goal of providing benefits internally and externally. Internal utilization consists of utilization for livestock operational costs. Meanwhile, external use for the welfare of orphans and poor people is also in line with the main objectives of the institution. And also produce a flow of productive cash waqf management system used for chicken and catfish farming. Keywords: cash waqf, application of waqf, livestock waqf